Associations of low sex hormone-binding globulin and androgen excess in early pregnancy with fasting and post-prandial hyperglycaemia, gestational diabetes, and its severity - Mustaniemi Sanna; Morin-Papunen Laure; Keikkala Eelina; Öhman Hanna; Surcel Heljä-Marja; Kaaja Risto; Gissler Mika; Eriksson Johan G.; Laivuori Hannele; Kajantie Eero; Vääräsmäki Marja (John Wiley and Sons Ltd, 2025)
Aims: We studied whether androgen excess and low sex hormone-binding globulin (SHBG) measured in early pregnancy are independently associated with fasting and post-prandial hyperglycaemia, gestational diabetes (GDM), and its severity.
Materials and methods: This nationwide case-control study included 1045 women with GDM and 963 non-diabetic pregnant controls. We measured testosterone (T) and SHBG from biobanked serum samples (mean 10.7 gestational weeks) and calculated the free androgen index (FAI). We first studied their associations with GDM and secondly with the type of hyperglycaemia (fasting, 1 and 2 h glucose concentrations during the oral glucose tolerance test), early-onset GDM (<20 gestational weeks) and the need for anti-diabetic medication.
Results: After adjustments for gestational weeks at sampling, pre-pregnancy BMI, and age, women with GDM had 3.7% (95% CI 0.1%-7.3%) lower SHBG levels, 3.1% (95% CI 0.1%-6.2%) higher T levels, and 4.6% (95% CI 1.9%-7.3%) higher FAI levels than controls. SHBG was inversely associated with fasting glucose, whereas higher FAI and T were associated with higher post-prandial glucose concentrations. Women with early-onset GDM had 6.7% (95% CI 0.7%-12.7%) lower SHBG levels and women who needed insulin for fasting hyperglycaemia 8.7% (95% CI 1.8%-14.8%) lower SHBG levels than other women with GDM.
Conclusions: Lower SHBG levels were associated especially with early-onset GDM, higher fasting glucose and insulin treatment, whereas androgen excess was associated with higher post-prandial glucose values. Thus, a low SHBG level may reflect the degree of existing insulin resistance, while androgen excess might impair post-prandial insulin secretion.